Formulation and Effectiveness Testing of A Virgin Coconut Oil (VCO) Moisturizing Cream For Treating Heel Xerosis - Irma Hartati; Asmaul Husna; Meliani Sukma Dewi; Arbaiyah (CV. Inara, 2026)
Xerosis of the heel of the foot is first shown by symptoms of dryness with the skin surface becoming scaly, hard, and uncomfortable. Continuous conditions will cause the surface of the skin to crack and crack which results in irritation and inflammation. Pure coconut oil is a fatty oil that can be used as a cream base and is able to prevent tissue damage and provide protection to the skin. To formulate a pure coconut oil moisturizing cream preparation and find out its effectiveness in treating xerosis on the heels of the feet. This study was conducted experimentally which included making cream preparations by adding virgin coconut oil, each with a concentration of F1 (2%), F2 (4%), F3 (6%) and F4 (8%) into the cream base moisturizer. As a blank, a moisturizing cream base without pure coconut oil (F0) is used. Tests on the virgin coconut oil moisturizing cream preparation included homogeneity test, emulsion type determination, pH determination, observation of the stability of the preparation after 12 weeks of storage, skin irritation test, test of the ability of the cream preparation to treat xerosis on the heels using 15 volunteers for one months of administration by applying moisturizing cream twice a day, by seeing a decrease in the xerosis level scale. Pure coconut oil can be formulated into a moisturizing cream preparation that is homogeneous and remains stable in storage for 4 weeks at room temperature with a w/m emulsion type. cream preparations show pH results that are in accordance with the physiological pH of the skin (6) and do not irritate the skin. Pure coconut oil cream preparations have the effect of curing xerosis on the heels of the feet in 15 volunteers for 4 weeks of use, preparations with a concentration of 8% are more effective than concentrations of 2%, 4% and 6%. Pure coconut oil (virgin coconut oil) can be formulated in the preparation of a moisturizing cream with a water/o emulsion type, the cream that is most effective in curing xerosis is produced from a concentration of 8% virgin coconut oil.